2011
DOI: 10.1068/i0416
|View full text |Cite
|
Sign up to set email alerts
|

A Reevaluation of Achromatic Spatio-Temporal Vision: Nonoriented Filters are Monocular, They Adapt, and Can be Used for Decision Making at High Flicker Speeds

Abstract: Masking, adaptation, and summation paradigms have been used to investigate the characteristics of early spatio-temporal vision. Each has been taken to provide evidence for (i) oriented and (ii) nonoriented spatial-filtering mechanisms. However, subsequent findings suggest that the evidence for nonoriented mechanisms has been misinterpreted: those experiments might have revealed the characteristics of suppression (eg, gain control), not excitation, or merely the isotropic subunits of the oriented detecting mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…For binocular presentations at low spatial frequencies, the binocular pathways have a summation advantage over the monocular pathway and their response may determine threshold. Similar methods have revealed isotropic responses in achromatic vision under conditions of low spatial and high temporal frequency, which also appear to be monocular (Meese & Baker, 2011).…”
Section: Monocular Versus Binocular Summationmentioning
confidence: 67%
See 2 more Smart Citations
“…For binocular presentations at low spatial frequencies, the binocular pathways have a summation advantage over the monocular pathway and their response may determine threshold. Similar methods have revealed isotropic responses in achromatic vision under conditions of low spatial and high temporal frequency, which also appear to be monocular (Meese & Baker, 2011).…”
Section: Monocular Versus Binocular Summationmentioning
confidence: 67%
“…The psychophysical approach of measuring subthreshold summation of grating stimuli at different orientations has been used to demonstrate orientation tuning for achromatic vision under a wide range of conditions (Kulikowski & King-Smith, 1973;Meese & Baker, 2011;Phillips & Wilson, 1984;Sachs et al, 1971). For achromatic stimuli, the lack of contrast summation within the visual system for orthogonal grating stimuli that are physically combined on the screen has been considered key psychophysical evidence for the presence of orientation tuning in the human visual system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an arrangement predicts a triplet of pedestal masking functions, similar to those found here (see Figure A1d in Appendix A). However, there is little or no evidence for such broad tuning at this low level in the hierarchy in the spatial domain (Baker & Meese, 2011a) or in the orientation domain (see Meese & Baker, 2011b, for a review), where receptive fields in the primary visual cortex (filter elements) have a small number of lobes (i.e. are selective to very few stimulus cycles) and are orientation tuned (DeValois & DeValois, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In the event that AIB is the result of the same adaptation processes as those observed using classical methods, then AIB and threshold paradigms should show similar stimulus dependencies. It is well known that the reduction in contrast sensitivity that follows flicker adaptation is highly contingent upon the relative orientation of adaptor and test (Cass et al 2012;Meese and Baker 2011), with most potent threshold elevation observed when adaptor and test are similar. Interestingly, this orientation-specific threshold elevation is evident regardless of whether one adapts and tests with the same eye or with different eyes.…”
Section: Introductionmentioning
confidence: 99%